2008
DOI: 10.1097/bcr.0b013e31815f366c
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Burn Care Facilities in the United States

Abstract: This historical review documents the establishment and current status of specialized burn care facilities opened in the United States since 1947, describes trends in their physical configuration and burn bed availability and discusses the terms used to classify those facilities. Lists of active burn care facilities were reviewed, including primarily the Burn Care Resource directories of the American Burn Association, which date back to 1976, along with the results of special surveys carried out by the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…However, there were significant changes in the distribution of patients across income quintiles over the interval of study; the proportion of patients in the lowest income quintile decreased from 35% to 16%, while the proportion of patients in the middle two quintiles (23) increased from 29% to 55%. The proportion of patients in the highest two quintiles (45) did not change significantly, representing approximately 25–30% of all patients each year.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…However, there were significant changes in the distribution of patients across income quintiles over the interval of study; the proportion of patients in the lowest income quintile decreased from 35% to 16%, while the proportion of patients in the middle two quintiles (23) increased from 29% to 55%. The proportion of patients in the highest two quintiles (45) did not change significantly, representing approximately 25–30% of all patients each year.…”
Section: Resultsmentioning
confidence: 91%
“…These improvements have been attributed, in part, to a dedicated, multidisciplinary approach to the care of burn injury, prompting efforts to develop regional systems for the care of burn-injured patients(3,4). While there is evidence in other areas of surgery and medicine that regionalization or concentration of care improves outcomes, there are limited data available relevant to the patient with major burn injury(59).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several studies have demonstrated that patients who receive optimal burn care at verified centers may have a better functional outcome after discharge. (5, 15) This may provide an opportunity for the burn community to educate and reinforce transfer criteria to non-burn hospitals, as well as for CMS to consider whether payment for treatment of large burns outside of burns centers is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our study was limited to only patients who presented to major burn centers. However, the great majority of MThBI survivors receiving tissue autograft are treated at such centers [4]. Another potential limitation is the influence of peri-assessment activities (occupational therapy, dressing changes, etc.)…”
Section: Discussionmentioning
confidence: 99%